Water Defluoridation Using Modify Zeolite by Al+3 Ions and Nanoscale Zero-Valent Iron (nZVI) in a Fixed Bed Column - Kourosh Rahmani; Hasan Rahmani; Khalilollah Moeinian; Mansour Sarafraz; Ayat Rahmani (Iranian Journal of Health, Safety and Environment, 2019)
Removal of the ﬂuoride ion of drinking water requires an effective technique. In study zeolite clinoptilolite by Al+3ions and nanoscale iron (nZVI) modify was used to remove fluoride from water. Contact was done by a fixed bed absorbent column. In this column, experiments were carried out using aqueous solutions and drinking water with mass. The dynamics of the adsorption process were fitted to Langmuir and Freundlich models. The results showed that highest uptake capacities 1.14 and 2.4mg/g for the modified zeolitic Al and nanoscale iron (nZVI) respectively, were obtained with a 5g mass column, an inlet 10 mg/L fluoride solution, and a flow rate of 3mL/min, but the sorption capacities decreased when drinking water used. Experimental data were fitted to both models Langmuir and Freundlich, and the methods indicated that these materials are suitable for the removal of fluoride from water in fix bed systems. In general, it can be concluded that modified zeolite clinoptilolite with fixed bed an effective and economical method to remove fluoride from groundwater.